Development of Educational Games for The Introduction of Fruits and Vitamins - Rachman, Andy; Purwanto, Mochamad Yuliadi; Nugroho, Hendro (Journal of Educational Science and Technology (EST), 2019)
Indonesia is one of the developing countries with the world's most abundant fruit and vegetable production. Indonesia is supported by geographical conditions that have two seasons, namely summer and rainy season. This condition causes fruits and vegetables to flourish in Indonesia. Fruit is a healthy food source for humans. Fruit is very beneficial for humans and contains lots of vitamins. The introduction of fruit benefits must be started early on from children. From the results of the pre-test, it found that there were still 32% of elementary school students who knew of the vitamins contained in the fruit. To overcome this, researchers made an educational game application for the introduction of fruit and vitamins based on Android. From the results of the post-test, 72% of students understood the type of vitamin on the fruit. From the results of this post-test, the application developed can help improve children's abilities by 39% from the prior state. In terms of application usability, get an average rating of 82%. Appraisal of application the five factors: understandability, learnability, operability, attractiveness, and usability compliance with the percentage values of 81%, 77%, 76%, 84%, and 93% respectively.